A SOLAR ASSITED DRYING SYSTEM FOR GREEN TEA - M. Yahya (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2011)
Indonesia being situated near the equator receives abundant solar radiation and having characterized by an average daily solar radiation of about 600-700W/m2 . This could be contributed as energy sources for drying green tea. This paper present the experimental studies conducted on the herbal tea or green tea using a solar assisted drying system. The drying system has an array of collector with the size 13.8 m2 . The fresh tealeaves form the plantations are first soaked I warm water for five minutes. Next, Water from the tealeaves will be drained out and dried in the chamber. The collector is of the V-Groove type. The system has two fans to circulate air. A 10 kW auxiliary heater is also included and will be on if the temperature of the drying chamber is less than the specified preset temperature of 50oC. A drying chamber of 55oC can be reached at solar radiation levels of 600-700 Wm2 and ambient temperature of 27-34oC. The flow rate is fixed at 15.1 m3 /min. The initial moisture content is 87% (wet basis) and the final moisture content is 54% (wet basis). A total of 12 hours of drying time is required where solar energy contribute about 56% the total energy requirement.